PRINSIP KOMUNIKASI PEMBANGUNAN DALAM PENGELOLAAN SAMPAH BERKELANJUTAN (STUDI KASUS: BANK SAMPAH INDUK RUMAH HARAPAN UMAT, DEPOK) - Lindawati, Sri; Vahista, Salwa Lila (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
The waste problem in urban areas demands a sustainable management strategy that involves active community involvement. One emerging approach is community-based waste management through the existence of a waste bank. This study aims to analyze the application of development communication principles in supporting sustainable waste management at the Main Waste Bank (BSI) of Rumah Harapan Umat (Rumah Harum), Depok City. This study focuses on five main principles: sustainability, community participation, collaboration, two-way dialogue and communication, and empowerment. The study uses a descriptive qualitative approach with a case study method. Data collection was conducted through in-depth interviews, observations, and documentation studies of waste management activities at BSI Rumah Harum. Data analysis focused on how development communication strategies were designed and implemented to encourage changes in community behavior in waste management. The results show that BSI Rumah Harum applies sustainability principles through circular economy education that adds value to waste. The principle of community participation is realized through active community involvement in waste sorting from the source, while the principle of collaboration is reflected in the synergy between BSI, local governments, and the private sector. In addition, the principle of dialogue and two-way communication is implemented through regular forums and the use of social media as a means of conveying customer aspirations. Meanwhile, the principle of empowerment is evident in the increased economic capacity and independence of communities through a waste savings system. This study concludes that the integration of these five development communication principles is a key factor in building a sustainable urban waste management ecosystem as a agen of changes.